RECOVERY BISNIS ZENZY FAMOUS DENGAN PENERAPAN ANALISIS SWOT DAN OPTIMALISASI PENGELOLAAN LAPORAN KEUANGAN - Apriliani, Safira; Algata, Agidia Magrisa; wanto, Pur; Kristayana, Oktavia Eka; Tiffany, Alvionita; Nurkholifah, Iis Lia; Taurisyana, Anis; Pramono, Joko (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, yet many have struggled due to the impact of the Covid-19 pandemic. One affected MSME is Zensy Famous, a fashion business experiencing a decline in revenue and difficulties in financial management. This study aims to support the business recovery of Zensy Famous by applying SWOT analysis and optimizing financial report management. The methodology includes initial analysis, problem identification, SWOT analysis, financial management training, as well as marketing and branding strategies. The results of this community service activity indicate that implementing a SWOT-based strategy helps Zensy Famous identify its strengths and business opportunities while addressing its weaknesses and external threats. Additionally, financial report optimization improves financial management efficiency. With enhanced digital marketing and branding strategies, Zensy Famous is expected to strengthen its competitiveness in the creative industry and achieve sustainable business growth.